Effect of oxygen supply on flavor formation during continuous alcohol-free beer production : a model study - Lehnert, Radek (2008)
The influence of oxygen supply on the formation and conversion of the most important flavor compounds during continuous, alcohol-free beer production was studied in a complex model medium. The medium contained inorganic salts, nutrients, and aldehydes (hexanal, 2-methyl propanal, 3-methyl butanal, and furfural) and mimicked real brewery wort, with the advantage of a constant composition. Fermentation experiments were carried out in a continuously operating gas-lift reactor, with brewing yeast immobilized on spent grains. The formation (ethanol, higher alcohols, esters, vicinal diketones, and acetaldehyde) and reduction (aldehydes) of flavor-active compounds at different aeration rates were observed. The results suggest that the oxygen supply represents an influential tool for controlling the degree of fermentation and flavor formation carried out by an immobilized biocatalyst. Under optimal oxygen supply conditions in the continuously operating gas-lift reactor, it was possible to obtain a fermented model medium with a composition approaching that of commercial alcohol-free beers produced by batch process.